2020
DOI: 10.3390/microorganisms8111679
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics of Pathogenic Clavibacter michiganensis subsp. michiganensis Strains from Chile Reveals Potential Virulence Features for Tomato Plants

Abstract: The genus Clavibacter has been associated largely with plant diseases. The aims of this study were to characterize the genomes and the virulence factors of Chilean C. michiganensis subsp. michiganensis strains VL527, MSF322 and OP3, and to define their phylogenomic positions within the species, Clavibacter michiganensis. VL527 and MSF322 genomes possess 3,396,632 and 3,399,199 bp, respectively, with a pCM2-like plasmid in strain VL527, with pCM1- and pCM2-like plasmids in strain MSF322. OP3 genome is composed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 69 publications
5
31
0
Order By: Relevance
“…Cluster analysis using virulence gene sequences showed the same strain grouping of strains obtained in previous analysis [15,16,28], except for the pelA1 gene, wherein the strain VQ519 separated from the group of strains belonging to ST32. Some studies of variability of virulence genes have reported low polymorphism values.…”
Section: Discussionsupporting
confidence: 68%
“…Cluster analysis using virulence gene sequences showed the same strain grouping of strains obtained in previous analysis [15,16,28], except for the pelA1 gene, wherein the strain VQ519 separated from the group of strains belonging to ST32. Some studies of variability of virulence genes have reported low polymorphism values.…”
Section: Discussionsupporting
confidence: 68%
“…The strain BmP21 that was isolated from the phyllosphere of Berberis sp. is closely related to Clavibacter michiganensis [ 44 , 62 , 63 ]. Both strains HsR18 and BmP21 were discarded for further analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Members of the Frondihabitans genus has only been associated with plants and lichens [ 96 , 97 , 98 , 99 , 100 ]. On the other hand, some members of the Xanthomonas and Clavibacter genera are phytopathogens, which are in the rhizosphere, the phyllosphere, and the endosphere of different plants [ 44 , 63 , 101 , 102 ]. In the present study, the bacterial strains that are closely related to phytopathogens, Xanthomonas sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in a re-classification study, some of the subgroups of C. michiganensis mentioned above have been given the consideration of new species. These new species were called as Clavibacter capsici, Clavibacter insidiosus, Clavibacter nebraskensis, Clavibacter sepedonicus (Li et al 2018;Méndez et al 2020). Although the tomato is the primary natural host of Cmm, peppers (Capsicum annuum) and eggplants (Solanum melongena) can also be infected in the field (Yim et al 2012).…”
mentioning
confidence: 99%